Capital Structure And Profitability: An Empirical Study Of Manufacturing Firms Listed On The Stock Exchange - R. Indrawan,; Mutmainah,; Verawaty, (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
Capital structure refers to the specific combination of debt and equity that a firm utilizes to finance its operations and growth (Titman & Wessels, 1988). A firm’s choice between debt and equity financing can have profound implications for its operational flexibility, tax obligations, and financial stability. This study adopts a systematic literature review (SLR) approach to examine the relationship between capital structure and profitability among manufacturing firms listed on stock exchanges. A systematic literature review enables researchers to identify, evaluate, and synthesize existing empirical studies in a transparent and replicable manner. This systematic literature review has examined the complex relationship between capital structure and profitability among manufacturing firms listed on various stock exchanges worldwide. The findings indicate that there is no universally consistent relationship between leverage and profitability. Instead, the nature of the relationship is influenced by factors such as firm size, industry sub-sector, geographic location, and the prevailing economic and institutional environments